Impact of Hyperkalemia and Worsening Renal Function on the Use of Renin Angiotensin Aldosterone System Inhibitors in Chronic Heart Failure With Reduced Ejection Fraction. Issue 3 (14th July 2017) - Pitt, B; Rossignol, P
Abstract : Patients with heart failure (HF) and reduced ejection fraction (HFREF) are at increased risk of death and hospitalizations for HF. Numerous registries have reported a large and persistent gap between real‐life practice in the use of life‐saving evidence‐based therapies, such as renin angiotensin system inhibitors, beta blockers, mineralocorticoid receptor antagonists (MRAs), and recommended practices in international guidelines. The fears of inducing hyperkalemia and/or worsening renal function are the main triggers of this underuse.